Hubungan Tipe Pola Asuh Orang Tua, Single Parent, Jenis Kelamin dan Kecenderungan Post-Traumatic Stress Disorder (PTSD) dengan Kejadian Depresi Pada Siswa di SMA Negeri 2 Mataram - Antari, Ni Kadek Widya; Syuhada, Irwan; Handayani, Wendy; Dahlia, Yolly (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT A common mental health disorder in adolescents is depression. Depression is a multifactorial disorder, namely biological factors, psychological or personality factors, genetic factors and psychosocial factors. Objective: Analyzing the relationship between the type of parenting, single parent, gender, and the tendency of Post-Traumatic Stress Disorder (PTSD) with the incidence of depression in students at SMA Negeri 2 Mataram. To analyze the relationship between parenting type, single parent, gender, and Post-Traumatic Stress Disorder (PTSD) tendency with the incidence of depression in students at Senior High School 2 Mataram. Observational analytic quantitative research with a cross-sectional study design. The research was conducted at SMA Negeri 2 Mataram on Monday, November 20, 2023. The sampling technique used total sampling with a sample size of 102 respondents. Data were analyzed using the Spearman Rank correlation test with a significance value limit (p-value) <0.05. The results showed that the majority were 16 years old (38.2%), the first child (30.4%), and lived with the mother (74.5%), experienced minimal depression (40.2%), had a permissive type of parenting (38.2%), divorced parents died (59.8%), female gender (58.8%), and potential PTSD (61.8%). Bivariate analysis showed that there was a relationship between parenting patterns with depression (p=0.000), single parent with depression (p=0.000), gender with depression (p=0.003), and PTSD tendency (p=0.000) in students of Senior High School 2 Mataram. Parenting type, single parent¸ gender, and Post-Traumatic Stress Disorder (PTSD) tendency are associated with depression in students of Senior High School 2 Mataram. Keywords: Depression, Parenting Type, Single Parent, Gender, Post-Traumatic Stress Disorder (PTSD).  ABSTRAK Gangguan kesehatan mental yang sering terjadi pada remaja adalah depresi. Depresi merupakan gangguan yang bersifat multifaktorial, yakni faktor biologis, faktor psikologis atau kepribadian, faktor genetik dan faktor psikososial. Menganalisis hubungan antara tipe pola asuh orang tua, single parent, jenis kelamin, dan kecenderungan Post-Traumatic Stress Disorder (PTSD) dengan kejadian depresi pada siswa di SMA Negeri 2 Mataram. Penelitian kuantitatif analitik observasional dengan desain penelitian cross sectional study. Penelitian dilaksanakan di SMA Negeri 2 Mataram pada hari Senin, 20 November 2023. Teknik pengambilan sampel menggunakan total sampling dengan besar sampel 102 responden. Data dianalisis dengan uji korelasi Rank Spearman dengan batas nilai signifikansi (p-value) < 0,05. Hasil penelitian menunjukkan mayoritas berusia 16 tahun (38,2%), anak pertama (30,4%), dan tinggal bersama ibu (74,5%), mengalami depresi minimal (40,2%), memilki tipe pola asuh orang tua permasif (38,2%), status orang tua bercerai meninggal (59,8%), jenis kelamin perempuan (58,8%), dan berpotensi PTSD (61,8%). Analisis bivariat menunjukkan terdapat hubungan pola asuh orang tua dengan depresi (p-value=0,000), single parent dengan depresi (p-value=0,000), jenis kelamin dengan depresi (p-value=0,003), dan kecenderungan PTSD (p-value=0,000) pada siswa SMA Negeri 2 Mataram.Tipe pola asuh orang tua, single parent¸ jenis kelamin, dan kecenderungan Post-Traumatic Stress Disorder (PTSD) berhubungan dengan depresi pada siswa SMA Negeri 2 Mataram. Kata Kunci: Depresi, Tipe Pola Asuh Orang Tua, Single Parent, Jenis Kelamin, Post-Traumatic Stress Disorder (PTSD).